Resilience among children and young people in impoverished urban areas in Kampala: strengths and the importance of context - Richardson, Anna (2017)
For social workers working with at risk populations, understanding the dynamic process of resilience presents an opportunity to enhance positive adaptation and provide adequate, contextually sensitive policy and practice to help fulfil the capacities of children and young people. Yet, there are limited studies examining this construct in the Ugandan context, particularly the contextually and culturally bound pathways navigating towards resilience despite adversity. Using a mixedmethod approach, this study aimed to; examine the dynamic nature of resilience as it relates to children and young people in impoverished urban areas in Kampala, analyse the factors that influence resilience processes and document the understanding of resilience as a construct among key stake holders. The method included dialogue sessions, administration of the Child and Youth Resilience Measure 28 item (CYRM-28), and semi-structured interviews with key informants. The children and young people in the study (n = 135; m = 47, f = 88) ranged from 10-24 years across eight geographic areas of urban impoverishment around Kampala. Findings suggest that children and young people in urban poor contexts demonstrate resilience processes, scoring significantly higher on CYRM- 28 than normative data (p = 0.00) and had unique ways to navigate and negotiate resources for positive adaptation despite adversity. According to this study children and young people in urban contexts rely frequently on their own abilities and skills to navigate their way to the resources that they need. Cooperation, problem solving, sense of belonging and social and practical skill development were all important for the sample population in adapting well despite the adversities that they faced. The combined analyses of the quantitative and qualitative components of the study suggest resilience is a highly relevant construct for application in policy and social work practice for children and youth in impoverished urban contexts.